Makueni Farmer Field Day - CGIAR Research Program on Climate Change, Agriculture and Food Security (2015)
On 28 and 29 January 2015 Farmers from CCAFS climate-smart villages and the wider Makueni region, attended the two farmer field days organized by the CGIAR Research Program on Climate Change, Agriculture and Food Security (CCAFS), East Africa and other partners working in Makueni. Farmers learned about pearl millet, sorghum, legumes and cassava technologies and later on went to Josephine Sammy’s farm for onsite trials. Photos S.Kilungu (CCAFS).